Mastisis study in dairy cattle in Baturraden - Maryono Agus (Hemera Zoa, 1991)
A total of 56 catle in Baturraden were examined. From these animals, 41 (73.2%) had subclinical mastisis. Staphylococcus epidermis organism were isolated from cultures prepared from positive milk samples. Other bacteria isolated were Staphylococcus aureus and Escherichia coli. Sensitivity test revealed all isolates were sensitive to erytthromycin, methicillin and penicillin. Therefore, these antibodies should become the drugss of choice for the treatment of masitis in Baturraden.